Chronic stress from adolescence to adulthood increases adiposity and anxiety in rats with decreased expression of Krtcap3 - Szalanczy, Alexandria M.; Fitzpatrick, Mackenzie; Beeson, Angela; Bui, Trangdai; Dyson, Christina; Eller, Seth; Landry, Julia; Scott, Christina; Grzybowski, Michael; Klotz, Jason; Geurts, Aron M.; Weiner, Jeff L.; et al. (Frontiers in Genetics, 2024)
We previously identified Keratinocyte-associated protein 3, Krtcap3, as a novel adiposity gene, but subsequently found that its impact on adiposity may depend on environmental stress. To more thoroughly understand the connection between Krtcap3, adiposity, and stress, we exposed wild-type (WT) and Krtcap3 knock-out (KO) rats to chronic stress then measured adiposity and behavioral outcomes. We found that KO rats displayed lower basal stress than WT rats under control conditions and exhibited metabolic and behavioral responses to chronic stress exposure. Specifically, stress-exposed KO rats gained more weight, consumed more food when socially isolated, and displayed more anxiety-like behaviors relative to control KO rats. Meanwhile, there were minimal differences between control and stressed WT rats. At study conclusion stress-exposed KO rats had increased corticosterone (CORT) relative to control KO rats with no differences between WT rats. In addition, KO rats, independent of prior stress exposure, had an increased CORT response to removal of their cage-mate (psychosocial stress), which was only seen in WT rats when exposed to chronic stress. Finally, we found differences in expression of the glucocorticoid receptor, Nr3c1, in the pituitary and colon between control and stress-exposed KO rats that were not present in WT rats. These data support that Krtcap3 expression affects stress response, potentially via interactions with Nr3c1, with downstream effects on adiposity and behavior. Future work is necessary to more thoroughly understand the role of Krtcap3 in the stress response.